USE OF CODOMINANT PROTEIN AND DNA MARKERS IN IDENTIFICATION OF F1 HYBRID PROGENIES IN SOYBEAN (Experimental biology, 2023)
Hybridization has been and remains the main method of creating an initial genetic pool for breeding, from which the breeder selects new breeding lines, varieties, and hybrids that meet the criteria. Soy is an obligate autogamous crop, the forced hybridization of which largely depends on the skill and experience of the breeder. One of the problems of inter variety  hybridization of soybeans is the identification of true hybrid plants and the elimination of "false" hybrids at the very beginning of the breeding process. Morphological differences between parental forms are not sufficient to control the heterozygosity of the first generation hybrids, since the number of such indicators is limited and many of them have a dominant manifestation. The advantage of protein and molecular markers is their polyallelicity and codominance. The aim of the research was to identify the parental forms of the soybean hybridization nursery and to identify codominantly inherited protein and DNA markers for their use in the recognition of heterozygous soybean hybrids. The studies used: SDS-PAGE electrophoresis of soybean seed storage proteins, PCR analysis of soybean DNA with 11 SSR markers.Parental lines with a specific composition of glycinins, storage proteins of soybean seeds, have been established. For 17 crossing schemes of the Victory soybean variety used as a mother form with different samples of the working collection, SSR markers were identified that are promising in the selection of F1 hybrids. The control of heterozygosity of hybrid lines on the basis of protein and DNA level markers will expand the possibilities of hybridization and will lead to the involvement of valuable traits and new useful combinations of genes in the created lines into domestic soybean breeding.
Keywords: soybean, hybridization, heterozygosity, codominance, protein and molecular markers